PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN - Lindawati, Amelia (Jurnal Akuntansi Kontemporer, 2010)
This study aims to examine the effect of corporate governance mechanism that consists of managerial ownership, institutional ownership, and size of the board of directors on the financial performance through the agency cost. The object of this research is the manufacturing companies listed in Indonesia Stock Exchange during the period 2007-2009. The sample used in this study as many as 41 companies selected by purposive sampling method. Secondary data obtained from the company's annual financial statements and then processed using the method of path analysis. The results showed that managerial ownership has no effect on financial performance through the agency cost, while institutional ownership and board size effect on financial performance through the agency cost.